Determinants and dynamics of current account reversals: an empirical analysis - Roman Liesenfeld; Guilherme V. Moura; Jean-François Richard (Kiel University, Department of Economics, 2009)
We use panel probit models with unobserved heterogeneity, state-dependence and serially correlated errors in order to analyze the determinants and the dynamics of current-account reversals for a panel of developing and emerging countries. The likelihood-based inference of these models requires high-dimensional integration for which we use Efficient Importance Sampling (EIS). Our results suggest that current account balance, terms of trades, foreign reserves and concessional debt are important determinants of current-account reversal. Furthermore, we find strong evidence for serial dependence in the occurrence of reversals. While the likelihood criterion suggest that state-dependence and serially correlated errors are essentially observationally equivalent, measures of predictive performance provide support for the hypothesis that the serial dependence is mainly due to serially correlated country-specific shocks related to local political or macroeconomic events.
Keywords: C15; C23; C25; F32; 330; Panel data; dynamic discrete choice; importance sampling; Monte Carlo integration; state dependence; spillover effects; Leistungsbilanz; Zahlungsbilanzungleichgewicht; Terms of Trade; Währungsreserven; Auslandsverschuldung; Schätzung; Panel; Entwicklungsländer; Schwellenländer